Fine grained access control using H-KCABE in cloud storage. (2021) - Sangeetha, M.; Vijayakarthik, P.; Dhanasekaran, S.; Murugan, B.S.
Abstract: Cloud computing is used to store data in cloud storage through remotely. Cloud services can reach from small scale to large scale applications in low cost budget. Through these services users are able to access and retrieve data very constrainedly in low cost budget. It is used for producing data cloud service provider. It's taking care of data to keep confidentially from entrusted access. It reduces most of the cloud security problems. This is achieved by some firewalls, cryptographic algorithms, antivirus software. The above techniques could not product data effectively which is shared by enterprise users who confidentially maintain the data during transactions among worldwide. Through simple encryption algorithm we cannot provide fine grained access control to the data in cloud storage. But its different from perfomance, scalability, reliability and other security parameters of cloud computing. In this paper we propose H-KCABE encryption algorithm in HABE model with some small modification and make better performance by re-encryption process. Through this we can easily achieve fine grained access control of cloud data than existing technique.